2020
DOI: 10.1039/d0cc05944g
|View full text |Cite
|
Sign up to set email alerts
|

A concise route to MK-4482 (EIDD-2801) from cytidine

Abstract: A two-step route to MK-4482 (EIDD-2801, 1) was developed consisting of an esterification and hydroxamination of cytidine. The selective acylation and direct amination eliminate the need for protecting and activating...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
74
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(84 citation statements)
references
References 14 publications
(1 reference statement)
3
74
0
4
Order By: Relevance
“…sable de que la mayoría de los coronavirus, incluido el SARS-CoV-2, se muestren resistentes a muchos análogos, incluyendo la ribavirina y el 5-fluoruracilo [16,17]. Por lo tanto, los nuevos análogos han de ser capaces de inhibir a los coronavirus en presencia de la actividad de la nsp14-ExoN [14][15][16][17].…”
Section: Figuraunclassified
See 1 more Smart Citation
“…sable de que la mayoría de los coronavirus, incluido el SARS-CoV-2, se muestren resistentes a muchos análogos, incluyendo la ribavirina y el 5-fluoruracilo [16,17]. Por lo tanto, los nuevos análogos han de ser capaces de inhibir a los coronavirus en presencia de la actividad de la nsp14-ExoN [14][15][16][17].…”
Section: Figuraunclassified
“…Este profármaco posee una elevada biodisponibilidad oral y es fosforilado en el grupo N4hidroxilo a nivel del tracto gastrointestinal. Posteriormente es hidrolizado para dar lugar al fármaco original (EIDD-1931) que se distribuye a los diferentes tejidos para ser tri-fosforilado por las células eucariotas (forma activa) [15,17,18]. El compuesto tri-fosforilado presenta un amplio espectro antiviral frente a los virus ARN, tales como la gripe, Ebola, virus de la encefalitis equina venezolana y Coronavirus (MERS, SARS-1 y SARS-CoV-2) [17,18].…”
Section: El Ribonucleósido Análogo Molnupiravir (Mk-4482 O Eidd-280) Es El Isopropil-éster Del Compuesto ß-D-n4-hidroxicitidina (Fórmula unclassified
“…The transamination reaction of intermediate (10) to MK-8842 (7) was previously reported in 96% yield with 94% purity via column chromatography. 5 Previously, 70% aq. isopropanol was used as the solvent for this reaction; however, we chose to replace this with 70% aq.…”
Section: Previous Workmentioning
confidence: 99%
“…We hypothesized that the decreased solubility of butanol in water (as compared to the solubility of isopropanol in water) would decrease the amount of hydroxylamine salts present in the organic layer post-reaction, thus leading to a more facile purification. The optimization of this transamination reaction began by using 4.5 equivalents of hydroxylamine sulfate relative to starting material 10, 5 which displayed good conversion of 10 to desired product 7 after 22 hours (SI Section 4.1). In addition to desired product formation, side product N-hydroxycytidine (NHC, 15) was formed in this reaction in small quantities.…”
Section: Previous Workmentioning
confidence: 99%
“…[5] This was the only reported synthesis in the open literature until recently, when routes toward EIDD-2801 were reported that replaced uridine for cytidine. [6,7] In the original route, first an acetonide protection followed by selective esterification of the 5′-hydroxy group is performed in a one-pot fashion. Then, the molecule is activated by introduction of the 1,2,4-triazole moiety which is further displaced by hydroxylamine.…”
mentioning
confidence: 99%